Methodological considerations for estimating indirect costs in children and adolescents with chronic conditions: a scoping review - Anne Kitschen; Lulseged M. Asegu; Dirk Sauerland (BMC Pediatrics)
Abstract Background In children and adolescents, the prevalence of chronic diseases, e.g., obesity, asthma, and attention-deficit/hyperactivity disorder (ADHD), has increased in the last decades. These diseases have negative effects on patients and their families and pose a significant economic burden. Indirect costs related to caregivers’ lost workdays or children’s and adolescents’ missed education are likely to be high. However, there are no guidelines for measuring and valuing indirect costs in this population. Thus, this scoping review aims to examine methods in published articles, compare these approaches, and analyze benefits and shortcomings. Methods The systematic literature search was conducted in Medline, PsycINFO, Embase, NHS EED, and the HTA Database considering all articles from inception until 16 October 2024. Two researchers independently screened title, abstract, and full text. Cost-of-illness studies (COIs) reporting indirect costs for obesity, asthma, or attention-deficit/hyperactivity disorders (ADHD) in children and adolescents up to 24 years were included. Only studies published in English or German were considered. Methodological characteristics, measurement of indirect costs, cost components, data source, and costing methods were extracted. Results The literature search revealed 45 studies. Thirty-two articles on asthma, eight on ADHD, and five on obesity were included. While all studies included absenteeism, only a few assessed and valued unpaid work (31.1%) or presenteeism (13.3%). Overall, 88.9% of the studies considered indirect costs for caregivers. Additionally, 51.1% considered productivity losses for children and adolescents, with 47.8% of these studies assigning a monetary value to these losses. The largest share of studies (53.3%) considered indirect costs by measuring and valuing caregivers’ lost work time. Discussion In conclusion, various methodologies were used to consider indirect costs for chronic diseases in children and adolescents, underlining the need for standardization. This scoping review presents methodologies for incorporating indirect costs in COIs and other types of economic evaluations, which focus on children and adolescents and adopt a societal perspective. These indirect costs include both paid and unpaid activities, as well as absenteeism and presenteeism, not only for caregivers but also for children and adolescents themselves.